ANALYSIS OF STUDENTS LEARNING DIFFICULTIES IN ENGLISH CLASS OF VII MTs ATSARUS SALAFIYAH - Moh. Lasim; Moh. Rudiyanto (Universitas Madura, 2026)
The purpose of this research is to find out the types of students' learning difficulties in English subject in class VII MTs Atsarus Salafiyah. To find out the factors that cause students' learning difficulties in English subject in class VII MTs Atsarus Salafiyah. This research is a qualitative descriptive study. The research instruments used were interview guides and documentation. Data collection techniques, namely interviews and documentation. The triangulation used in this research is data triangulation.The results of this study resulted in students of class VII Atsarus Salafiyah experiencing 5 types of learning difficulties, the first type of difficulty is learning disorder which is characterized by a lack of self-confidence and bad peer relations. The second type of difficulty is learning disability which is characterized by low learning concentration, bad attitudes and behavior, less learning time, the third type of difficulty is learning dysfunction which is characterized by impaired vision, low level of intelligence, low memory. The fourth type of difficulty is slow learning which is characterized by low teacher competence, ineffective learning methods, inappropriate learning instruments, inadequate school facilities, inappropriate assignments. The fifth type of difficulty is the under achiever which is characterized by low interest in learning, lack of motivation to learn.